Quay crane performance improvement and lifecycle extension: retrofit determination – a case study - Sundaraja Perumal A Gothandapani; Mohd Nizam Ab Rahman; Hawa Hishamuddin (Penerbit Universiti Kebangsaan Malaysia, 2024)
Quay cranes (QCs) are critical equipment in Container Terminals and their performance determines the port operation efficiency in meeting operational Key Performance Indicators (KPIs). Considering 30-year lifespan of QCs and deteriorating reliability of the electrical control system, planning for timely retrofit of the QCs is critical. The paper aims to present a case study on how the performance of a batch of QCs, having more than 50% remaining lifespan, were analyzed and concluded to be retrofitted to address their deteriorating performance, high maintenance cost and obsolescence. The study methodology is based on quantitative data and employed a prospective longitudinal panel research design over sixteen years. eleven years of pre-retrofit and five years of post-retrofit operations, maintenance and financial data were collected. Convenient sampling technique was selected in this study as the QCs identified as samples were having reliability issues. The Correlation Analysis indicates strong positive correlation of more than 90% between Mean Time Between Failure, Mean Move Between Failure and Reliability KPIs. These KPIs have moderate positive correlations of about 50% with Availability KPI. These 4 KPIs have strong negative correlation of between -50% and -85% with Mean Time to Repair, Maintenance and Breakdown Repair Cost indicating performance degradation but increased maintenance and repair costs as shown by Trend Analysis. The 11-year pre-retrofit data has identified parameters to determine the QC retrofit prediction. The KPIs, obsolescence status, maintenance and breakdown repair cost can be used as the inputs to the future QC Retrofit Prediction Model development.